Baicalin Attenuates Oxygen–Glucose Deprivation/Reoxygenation–Induced Injury by Modulating the BDNF-TrkB/PI3K/Akt and MAPK/Erk1/2 Signaling Axes in Neuron–Astrocyte Cocultures - Li, Changxiang; Sui, Conglu; Wang, Wei; Yan, Juntang; Deng, Nan; Du, Xin; Cheng, Fafeng; Ma, Xiaona; Wang, Xueqian; Wang, Qingguo (Frontiers in Pharmacology, 2021)
Background: Baicalin, a candidate drug for ischaemic stroke, has been indicated to protect neurons by promoting brain-derived neurotrophic factor (BDNF). However, the cellular source of BDNF release promoted by baicalin and its detailed protective mechanism after ischaemia/reperfusion remain to be studied. The aim of this study was to investigate the neuroprotective mechanisms of baicalin against oxygen-glucose deprivation/reoxygenation (OGD/R) in a neuron and astrocyte coculture system and to explore whether the BDNF-TrkB pathway is involved. Methods and Results: A neuron-astrocyte coculture system was established to elucidate the role of astrocytes in neurons under OGD/R conditions. The results demonstrated that astrocytes became reactive astrocytes and released more BDNF in the coculture system to attenuate neuronal apoptosis and injury after OGD/R. Baicalin maintained the characteristics of reactive astrocytes and obviously increased the expression of cyclic AMP response element-binding protein (CREB) and the levels of BDNF in the coculture system after OGD/R. To further verify whether BDNF binding to its receptor tyrosine kinase receptor B (TrkB) was required for the neuroprotective effect of baicalin, the effect of ANA-12, an inhibitor of TrkB, on NA system injury, including oxidative stress, inflammation and apoptosis induced by OGD/R, was examined. The results showed that treatment of NA systems with ANA-12 significantly attenuated the neuroprotection of BCL. The phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) and mitogen-activated protein kinase (MAPK)/extracellular-signal-regulated kinase (ERK) pathways are two important downstream cascades of signalling pathways activated by BDNF binding to TrkB. We investigated the expression of TrkB, PI3K, Akt, MAPK and ERK. The results demonstrated that baicalin significantly increased the expression of TrkB, PI3K/AKT and MAPK/ERK. Conclusion: The neuroprotective effects of baicalin against oxidative stress, inflammation and apoptosis were improved by astrocytes, mainly mediated by increasing the release of BDNF and its associated receptor TrkB and downstream signalling regulators PI3K/Akt and MAPK/Erk1/2.